Mudanças climáticas: Desafios para a adaptaç\~ao nas regi\~oes metropolitanas brasileiras - Monise Terra Cerezini; César Nunes de Castro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– Climate change is an increasingly relevant topic in academic, diplomatic and government circles. The expected impacts of climate change on cities are varied. Such impacts may include: floods and damage caused by rising sea levels in coastal cities, damage to existing urban infrastructure caused by extreme weather events, damage to the health of the population, impacts on water availability and energy use etc. This article aims to investigate how the issue of adaptation to climate change has been incorporated into national urban planning. For this, the Urban Adaptation Index (IAU), proposed by Neder et al. (2021), was used to assess the level of preparation in Brazil's 81 legally definied Metropolitan Regions (RMs), 3 Integrated Development Regions (Rides) and 3 Urban Agglomerations (AGLOs). The results presented indicate that the different metropolitan regions of Brazil have different levels of adaptive capacity to climate change.
Keywords: Q54; Q58; 330; climate change; adaptation; metropolitan regions